A Study of Student Behavior in Waste Management at SMA Negeri 1 Jayapura - Semuel Jeujanan (Edumaspul: Jurnal Pendidikan, 2025)
This study explores student behavior in waste management at SMA Negeri 1 Jayapura, Indonesia, focusing on how knowledge, attitudes, social norms, and environmental factors influence sustainable waste practices. Using a qualitative descriptive design, the research gathered data through interviews, observations, and document analysis involving 20 students and four school staff members. Results revealed a discrepancy between students’ awareness of environmental cleanliness and their actual behavior, primarily influenced by inadequate infrastructure, limited monitoring, and inconsistent social modeling. The findings confirm the applicability of Ajzen’s Theory of Planned Behavior and Bandura’s Social Cognitive Theory in explaining how internal motivations interact with environmental and social contexts to shape pro-environmental actions. The study concludes that effective environmental education requires integrating experiential learning, peer influence, and cultural contextualization. Practical implications highlight the need for improved school facilities, participatory programs, and sustainable education policies to strengthen waste management practices in schools and foster long-term ecological responsibility among students.